Assessment of association between Salivary Alpha Amylase, Buffering capacity, dmft index, BMI and Socioeconomic Status in children with and without Early Childhood Caries- An analytical study - A. Tiwari, Siddeshwari; Shah, Preetam; M. Chaudhary, Shweta; S. Lakade, Laxmi; Jajoo, Shweta; Patil, Krishna (Journal of Neonatal Surgery, 2024)
Objectives:Early Childhood Caries is one of the most common chronic conditions in preschool-aged children. Salivary components such as alpha-amylase (sAA) and buffering capacity help maintain oral health by controlling pH and influencing microbial activity. Body Mass Index (BMI), and socioeconomic status (SES) may further impact caries risk. This study evaluated the associations between sAA, buffering capacity, BMI, SES, and dmft scores in children with and without ECC. Methods:A total of 78 children aged 3-6 years participated. Based on caries experience, they were categorized into an ECC group (n=39) and a caries-free group (n=39). The ECC group was further divided into three subgroups by dmft score: A (0-5), B (6-10), and C (≥11). BMI percentiles were determined using CDC growth charts, while SES was assessed using the Modified Kuppuswamy Scale (2017). Unstimulated saliva collected; sAA was quantified using ELISA, and buffering capacity was determined by titrating with 0.01 N HCl and measuring pH changes. Statistical analysis included descriptive measures and Pearson’s correlation. Results:Mean dmft values rose progressively across ECC subgroups: A (3.08 ± 0.76), B (8.38 ± 1.25), C (15.46 ± 2.88). Higher BMI was observed with greater caries severity, with overweight more common in Group C. Lower SES was linked to a higher dmft. Buffering capacity decreased as dmft increased, ranging from normal in Group A (3.62 ± 0.51) to low in Group C (1.62 ± 0.96). Mean sAA levels followed a similar declining pattern, from 2.9 ± 1.8 in Group A to 2.2 ± 1.2 in Group C. Correlation analysis showed strong positive association between dmft and BMI (r=0.646), strong negative association between dmft and buffering capacity (r=-0.708), and moderate negative association between BMI and buffering capacity (r=-0.409). Conclusion:Greater ECC severity was linked to higher BMI, reduced salivary buffering capacity, and lower sAA levels, with socioeconomic amplifying the risk. Assessing salivary markers alongside BMI and SES may enable early identification of children at elevated risk and support timely preventive strategies